2018
DOI: 10.1016/j.dsr2.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Seafloor authigenic carbonate crusts along the submerged part of the North Anatolian Fault in the Sea of Marmara: Mineralogy, geochemistry, textures and genesis

Abstract: Extensive seafloor authigenic carbonate crusts occur as pavements, mounds and chimneys along the North Anatolian Fault System (NAFS) in the Sea of Marmara. They are often covered or surrounded by patches of black Fe-sulphide-rich sediments, and associated with hydrocarbon-rich gas and brackishwater emissions in the 1250 m-deep deep basins and with deep saline formation waters and hydrocarbons emissions from mud volcanoes and anticlines on the 350 to 650 m-deep compressional highs. Please note that this is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 102 publications
(182 reference statements)
1
20
0
Order By: Relevance
“…However, there is no systematic relationship between gas composition and proximity to fault zones. For instance, thermogenic methane dominates fluid emissions over the top of the Central High and within the MMF deformation zone in the Western High (Bourry et al, 2008;Çağatay et al, 2017;Ruffine et al, 2017) but we showed that the distributions of seepages have different characteristics at both locations (broad leakage zone over an anticline vs. 2 km wide swath along the main fault). Close examination of the relationship between faults and gas emissions within seafloor deformation zones also shows that even at the 10-100 m scale of AUV maps and submersible observations (Figure 7 and Grall et al, this issue), many acoustic anomalies are not located on the outcrops of small faults.…”
Section: Gas Migration Pathways In Shallow Sedimentsmentioning
confidence: 52%
“…However, there is no systematic relationship between gas composition and proximity to fault zones. For instance, thermogenic methane dominates fluid emissions over the top of the Central High and within the MMF deformation zone in the Western High (Bourry et al, 2008;Çağatay et al, 2017;Ruffine et al, 2017) but we showed that the distributions of seepages have different characteristics at both locations (broad leakage zone over an anticline vs. 2 km wide swath along the main fault). Close examination of the relationship between faults and gas emissions within seafloor deformation zones also shows that even at the 10-100 m scale of AUV maps and submersible observations (Figure 7 and Grall et al, this issue), many acoustic anomalies are not located on the outcrops of small faults.…”
Section: Gas Migration Pathways In Shallow Sedimentsmentioning
confidence: 52%
“…gas hydrate is estimated to cover an area of about 55 km 2 today . Samples from water depths between 200 and 1,000 m represent sites with a possible link between hydrostatic pressure and hydrate dissociation (Çağatay et al, 2018;Crémière et al, 2013;Han et al, 2014;Himmler et al, 2016;Liebetrau et al, 2010Liebetrau et al, , 2014Mazzini et al, 2017;Prouty et al, 2016;Ruffine et al, 2013;Teichert et al, 2003;Tong et al, 2013;Yang, Chu, et al, 2018). 3. the average gas hydrate saturation estimated from pore water freshening analysis ranges from 45% to 55% of the total pore space we use 50% for calculation); 4.…”
Section: Estimating Past Methane Flux Caused By Gas Hydrate Dissociationmentioning
confidence: 99%
“…Using a simple model, we calculate methane flux as follows: Table S4 for detail) and seep carbonates in this study (red and blue circles; Table S3). Samples from water depths greater than 1,000 m (Aharon et al, 1997;Bayon, Loncke, et al, 2009;Bayon et al, 2013Bayon et al, , 2015Çağatay et al, 2018;Crémière et al, 2013;Feng et al, 2010;Himmler et al, 2015Himmler et al, , 2019Kutterolf et al, 2008;Lalou et al, 1992;Liebetrau et al, 2010Liebetrau et al, , 2014Mazumdar et al, 2009;Prouty et al, 2016;Watanabe et al, 2008) represent sites with a weak link between hydrostatic pressure and hydrate dissociation, whereas samples from water depths less than 200 m represent sites were hydrate dissociation was not involved (Aharon et al, 1997;Crémière, Lepland, Chand, Sahy, Kirsimäe, et al, 2016;Feng et al, 2010). Samples from water depths between 200 and 1,000 m represent sites with a possible link between hydrostatic pressure and hydrate dissociation (Çağatay et al, 2018;Crémière et al, 2013;Han et al, 2014;Himmler et al, 2016;Liebetrau et al, 2010Liebetrau et al, , 2014Mazzini et al, 2017;Prouty et al, 2016;Ruffine et al, 2013;Teichert et al, 2003;Tong et al, 2013;Yang, Chu, et al, 2018).…”
Section: Estimating Past Methane Flux Caused By Gas Hydrate Dissociationmentioning
confidence: 99%
“…The sediments in the vicinity of the seeps host living benthic Foraminifera, and a study from samples collected on the Central High and the Çınarcık Basin show that Bolivina vadescens and Globobulimina affinis are the two dominant species at the study areas (Fontanier et al, 2018). Three articles (Akhoudas et al, 2018;Çağatay et al, 2018;Teichert et al, 2018) deal specifically with the texture, mineralogical and isotopic compositions and genesis of authigenic carbonate crusts associated with cold seeps in the SoM. These studies demonstrate the use of crusts as archives of past fluid activity and possibly of earthquake activity.…”
Section: Introductionmentioning
confidence: 99%